2001
DOI: 10.1071/ea00029
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and developmental effects on the intrinsic properties of muscles as they relate to the eating quality of beef

Abstract: Abstract. The intrinsic properties (those extant at the time of slaughter) of bovine skeletal muscle as they relate to the subsequent quality attributes of beef are reviewed here. Attributes of bovine skeletal muscle that ultimately affect toughness, colour, fat content, flavour, juiciness, and nutritive value of beef are discussed. The dynamic nature of muscle development, particularly with regard to structure and composition, is highlighted. Variation in development of muscle structure and composition due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 188 publications
(225 reference statements)
0
26
0
3
Order By: Relevance
“…relevant to evaluate more precisely the link between "grain of meat" criteria and physico-chemical properties of muscles, as it is well known that muscular characteristics are significantly correlated with tenderness (Oddy, Harper, Greenwood, & McDonagh, 2001). Contrary to expectations (Purslow, 2005), the "grain of meat" concept is not significantly related to meat tenderness.…”
Section: Discussionmentioning
confidence: 98%
“…relevant to evaluate more precisely the link between "grain of meat" criteria and physico-chemical properties of muscles, as it is well known that muscular characteristics are significantly correlated with tenderness (Oddy, Harper, Greenwood, & McDonagh, 2001). Contrary to expectations (Purslow, 2005), the "grain of meat" concept is not significantly related to meat tenderness.…”
Section: Discussionmentioning
confidence: 98%
“…Jurie et al (2006) showed that the STN had a greater percentage of fasttwitch glycolytic fibers, whereas the LM had a greater percentage of slow-twitch oxidative fibers. Muscle fiber types are dynamic, constantly changing in proportion as the animal ages, but muscle type is a reflection of the energy requirements of the muscle (Hocquette et al, 1998;Oddy et al, 2001). Because the STN is involved in animal movement, it may have a greater energy re-quirement than the LM, which results in the STN having a greater proportion of glycolytic enzymatic activity.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Furthermore, pasture-finished domestic animals had significantly higher (P < 0.001) SFLT and ICST than feedlot-finished Korean and Japanese market animals averaging 23 and 24 months of age respectively, suggesting a growth path effect on meat quality. Other studies and reviews have attributed differences in meat quality between pasture and feedlot finishing to age at slaughter, growth path (Allingham et al 1998;Harper et al 1999;Oddy et al 2001;McKiernan and Wilkins 2009) and growth rate (Hearnshaw et al 1995;Perry et al 1999).…”
Section: Pasture V Feedlot Finishingmentioning
confidence: 99%
“…Growth path has an important influence on meat quality (Allingham et al 1998;Harper 1999;Oddy et al 2001;McKiernan and Wilkins 2009). Harper et al (1997) reported that a period of severe nutritional restriction in an animal's growth path can influence the connective tissue toughness of its meat for at least 150 days following restriction, possibly as a result of increased intramuscular collagen turnover (Allingham et al 1998).…”
Section: Subtropical V Temperate Finishing Environmentsmentioning
confidence: 99%